High-stiffness white polyester film and preparation method thereof

By using ABA three-layer coextruded structure and POE-g-GMA modified cycloolefin amorphous copolymer in the reflective film, the problem of easy folding of polyester reflective film in large-size backlight modules is solved, and a high-density and good stiffness reflective film is achieved, which simplifies the preparation process and reduces costs, while meeting the requirements of green and environmental protection.

CN119502516APending Publication Date: 2025-02-25HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411621640.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing polyester reflective films are prone to creases during use of large-size backlight modules, and adding functional layers to improve stiffness will lead to increased film thickness, affecting short OD applications, and the solvents used during coating can cause environmental harm.

Method used

A high-stiffness white polyester film with a three-layer coextruded structure is adopted. A POE-g-GMA-modified cycloolefin amorphous copolymer is used as an incompatible resin in the B layer, and combined with inorganic functional masterbatches, the stiffness and density of the reflective film are improved.

Benefits of technology

The high density and good stiffness of the reflective film are achieved, which avoids crease problems, and simplifies the preparation process, reduces costs, and does not require the use of harmful solvents, which meets the requirements of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133600380000061
    Figure BDA0005133600380000061
  • Figure BDA0005133600380000071
    Figure BDA0005133600380000071
  • Figure BDA0005133600380000081
    Figure BDA0005133600380000081
Patent Text Reader

Abstract

According to the high-stiffness white polyester film, the reflecting film is of an ABA three-layer co-extrusion structure, and the A layer is a dodging layer and comprises the following components in percentage by weight: 10-96% of functional master batch, 0-86% of polyester chips, 2% of antistatic master batch and 2% of flexibilizer; the layer B is a functional layer and comprises the following components in percentage by weight: 40-60% of incompatible resin master batch, 5-30% of inorganic functional master batch and 10-50% of polyester chips; the percentage content is weight percentage. The COC master batch is selected as the incompatible resin in the functional layer of the reflective film, and the prepared reflective film has the characteristics of high density and good stiffness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a reflective film, in particular to a high-stiffness white polyester film and a preparation method thereof. Background Art

[0002] In the LCD backlight module, the optical films included include diffusion film, brightening film, and reflective film. The main function of the reflective film is to reflect the light emitted by the backlight source to the diffusion film or light guide plate, increase the utilization rate of the backlight source, and reduce energy loss. The reflective films currently prepared are generally divided into metal reflective films and polyester reflective films. Because polyester reflective films are cheap, have excellent performance, and are simple to prepare, polyester reflective films account for more than 90% of the market. The preparation of polyester reflective films is generally to increase the reflectivity of the film by adding inorganic particles and incompatible resins. Among them, incompatible resins usually use polymethylpentene, and the prepared reflective film usually has a high reflectivity. For example, CN110927846B uses polymethylpentene, which has light density, high transparency, high melting point, and aging resistance, but its molecular chain is a flexible chain without rigid groups. The prepared reflective film has low density and insufficient stiffness, and is prone to creases during the use of large-size backlight modules. At present, in order to improve the stiffness of the reflective film and reduce crease defects, a coating is generally added to the substrate. For example, CN114779377B improves the crease resistance by coating a self-repairing layer and other functional layers on the base film. However, the thickness of the reflective film prepared after coating the functional layer increases, which is not conducive to the current application of short OD. In addition, the solvents used in the coating process are harmful to the environment and are not conducive to green and environmental protection development. Summary of the invention

[0003] In order to overcome the drawbacks of the prior art, the present invention provides a high-stiffness white polyester film and a preparation method thereof. The incompatible resin in the functional layer is selected from COC masterbatch, so that the prepared reflective film has the characteristics of high density and good stiffness.

[0004] The technical solution adopted by the present invention to solve its technical problem is:

[0005] A high-stiffness white polyester film, the reflective film is an ABA three-layer co-extrusion structure, the A layer is a uniform light layer, comprising the following percentages of components: 10-96% functional masterbatch, 0-86% polyester chips, 2% antistatic masterbatch and 2% toughening agent; the B layer is a functional layer, comprising the following percentages of components: 40-60% incompatible resin masterbatch, 8-40% inorganic functional masterbatch and 0-52% polyester chips; the percentages are weight percentages.

[0006] The above-mentioned high-stiffness white polyester film, the incompatible resin masterbatch is a cycloolefin non-crystalline copolymer modified by POE-g-GMA, and is made by processing 20% ​​cycloolefin non-crystalline copolymer, 3% POE-g-GMA and 77% PET chips through a venting twin-screw granulator.

[0007] The above-mentioned high-stiffness white polyester film, the cycloolefin non-crystalline copolymer is made by copolymerization of ethylene and norbornene monomer (NB) under the action of a metallocene catalyst system, the cycloolefin non-crystalline copolymer has a glass transition temperature of 140°C; a melt index MFR (2.16kg, 260°C) of 40g / 10min; and a yellowness index YI of 2.

[0008] The above-mentioned high-stiffness white polyester film, the inorganic functional masterbatch in the B layer is made of 60% titanium dioxide, 1% PEG-20000 and 39% PET chips through a venting twin-screw granulator, the titanium dioxide is rutile titanium dioxide, the particles are spherical, and the average particle size is 200nm.

[0009] In the above-mentioned high-stiffness white polyester film, the functional masterbatch in the A layer is at least one of silicon dioxide, titanium dioxide, calcium carbonate, barium sulfate, and aluminum oxide, preferably silicon dioxide, and the number average particle size thereof is 3.8 μm.

[0010] In the above-mentioned high-stiffness white polyester film, the antistatic masterbatch in the A layer is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; and the toughening agent is PETG.

[0011] The above-mentioned high-stiffness white polyester film, the polyester slice includes at least one of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate, preferably PET, and has a viscosity of 0.675 dl / g.

[0012] The above-mentioned high-stiffness white polyester film has a thickness of 50 to 300 μm for the reflective film.

[0013] A method for preparing a high-stiffness white polyester film, the preparation method comprising the following steps:

[0014] S1, casting: the polyester chips, inorganic functional masterbatch, and incompatible resin masterbatch in the B layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; at the same time, the polyester chips, antistatic agent, functional masterbatch, and toughening agent in the A layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; the raw materials of the B layer and the A layer are laminated into three layers in the die head, and then co-extruded from the die head mouth, and quickly attached to the surface of the cooling drum with the help of an electrostatic adsorption device to obtain an amorphous thick sheet;

[0015] S2, stretching film forming: the amorphous thick sheet obtained in step S1 is first preheated by a longitudinal stretching roller, and then longitudinally stretched 3.0-3.6 times between the stretching fast and slow rollers under the auxiliary heating of an infrared lamp, and a single-stretched film is obtained after cooling. The single-stretched film is introduced into the clamps on both sides of the transverse stretching entrance and clamped, and enters the transverse stretching system, transversely stretched 3.4-4.0 times, heat-set for 10-30 seconds, fully crystallized, and then the track is narrowed and cooled, and then trimmed, rolled, and slit to obtain a finished reflective film.

[0016] In the method for preparing the above-mentioned high-stiffness white polyester film, in the step S2, during the process from horizontal stretching heat setting to cooling, the heat setting temperature is 190-235°C; after crystallization, the track shrinks by 1%-5%, the track starts to shrink from the transition zone and ends in cooling zone 1, and the temperature gradually decreases during the process from heat setting to cooling; the temperature in the transition zone is 140-190°C, and the temperature in the cooling zone is 70-130°C.

[0017] The beneficial effects of the present invention are:

[0018] 1. The cyclic olefin copolymer used in the present invention has the advantages of high transparency, non-crystallization, high density, good temperature resistance, etc., and is modified by adding POE-g-GMA. POE-g-GMA and the cyclic olefin non-crystallization copolymer melt well, and there are double bonds in both POE and the cyclic olefin copolymer. Due to the mutual attraction of chemical bonds, POE can increase the toughness of cyclic olefins; GMA is a polar part and has good melting properties with PET. The addition of POE-g-GMA avoids the phenomenon of uneven melt discharge from the granulation die, thereby maintaining the integrity of the pores and preventing collapse, which is beneficial to improving reflectivity and reducing density.

[0019] 2. The incompatible resin of the present invention is a cycloolefin non-crystalline copolymer, the main chain of which contains a cyclic structure. A rigid group is introduced into the functional layer to improve the stiffness of the reflective film.

[0020] 3. The density of the reflective film prepared by the present invention is 0.85-1.10 g / cm 3, avoid too low density, the film will be soft and prone to creases, too high density will correspond to large stiffness, which is not conducive to subsequent cutting applications, and the film surface will warp; appropriate stiffness, 2.5~5mN·m, has good folding resistance, reduces the breakage rate in downstream use, and reduces production costs.

[0021] 4. The preparation method provided by the present invention has simple process, convenient operation, low cost, and is environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0022] In the B layer of the present invention, the incompatible resin masterbatch is a cycloolefin amorphous copolymer modified by POE-g-GMA, which is specifically made of 20% cycloolefin amorphous copolymer, 3% POE-g-GMA and 77% PET slices processed by a venting twin-screw granulator (hereinafter collectively referred to as COC masterbatch). The content of POE-g-GMA is 3%. If the content is too high, tailing is likely to occur during granulation; if the content is too low, the chemical bonding between the two substances is not strong, and the melt discharged from the die head is of different thicknesses.

[0023] Inorganic functional masterbatch is also added to the B layer, which is specifically made of 60% titanium dioxide, 1% PEG-20000 and 39% PET chips processed by a venting twin-screw granulator (hereinafter collectively referred to as TiO2 functional masterbatch). The titanium dioxide is rutile titanium dioxide, the particles are spherical, and the average particle size is 200nm.

[0024] The present invention controls the reflectivity by adjusting the addition amount of TiO2 masterbatch and COC masterbatch in the B layer, and the weighted average reflectivity reaches more than 95%.

[0025] The functional masterbatch in layer A is selected from at least one of silicon dioxide, titanium dioxide, calcium carbonate, barium sulfate, and aluminum oxide. Furthermore, the A layer is preferably silicon dioxide. In order to meet the uniform light properties of the film surface, the number average particle size of silicon dioxide is optimal at 3.8 μm. According to the content of inorganic particles in layer A, a reflective film with different uniform light properties can be prepared. The uniform light properties can be expressed by testing the gloss of the film surface. The uniform light properties are inversely proportional to the gloss, that is, the lower the gloss, the better the uniform light properties. The glossiness of the reflective film is controlled by adjusting the amount of silicon dioxide added, and the 60° glossiness is adjustable within the range of 20 to 100 GU.

[0026] The preferred silica masterbatch is FG613, which is selected from Sinopec Yizheng Chemical Fiber Co., Ltd. The amount of FG613 added is 10-96% of the total weight of the A layer, and the above percentages are weight percentages.

[0027] The antistatic masterbatch in layer A is selected from octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; the added amount accounts for 2% of the total weight of layer A, and the above percentage is weight percentage; the added amount should not be too much. Too much added amount will easily accelerate the precipitation speed of oligomers at the die head and increase the amount, which will easily cause defects such as die head lines and oligomers on the film surface.

[0028] The total thickness of the reflective film of the present invention is 50-300 μm, the thickness of the reflective film for small and medium sizes is 50-150 μm, and the thickness of the reflective film for large sizes is 150-300 μm.

[0029] "%" in the present invention, unless otherwise specified, refers to weight percentage.

[0030] Film making process of the present invention:

[0031] S1, casting: the polyester chips, inorganic functional masterbatch, and incompatible resin masterbatch in the B layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; at the same time, the polyester chips, antistatic agent, functional masterbatch, and toughening agent in the A layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; the raw materials of the B layer and the A layer are laminated into three layers in the die head, and then co-extruded from the die head mouth, and quickly attached to the surface of the cooling drum with the help of an electrostatic adsorption device to obtain an amorphous thick sheet;

[0032] Furthermore, the B layer cast sheet can also be processed by a single screw extruder. When a single screw extruder is used for processing, the raw materials need to be pre-crystallized and dried before entering the extruder to remove moisture from the raw materials and prevent the polymer from hydrolyzing or generating bubbles during high temperature processing, thereby reducing product performance.

[0033] S2, stretching film forming: the amorphous thick sheet obtained in step S1 is first preheated by a longitudinal stretching roller, and then longitudinally stretched 3.0-3.6 times between the stretching fast and slow rollers under the auxiliary heating of an infrared lamp, and a single-stretched film is obtained after cooling. The single-stretched film is introduced into the clamps on both sides of the transverse stretching entrance and clamped, and enters the transverse stretching system, transversely stretched 3.4-4.0 times, heat-set for 10-30 seconds, fully crystallized, and then the track is narrowed and cooled, and then trimmed, rolled, and slit to obtain a finished reflective film.

[0034] Furthermore, during the longitudinal and transverse drawing processes, the incompatible resin forms a large number of bubbles in the core layer.

[0035] Furthermore, during the process of heat setting and cooling of transverse drawing, the setting temperature is 190-235℃, so that the film can be fully crystallized; the transverse drawing track is narrowed in the transition zone (the transition zone between heat setting and cooling, not the buffer zone) and the cooling zone to control the transverse heat shrinkage, and the track shrinkage is 1%-5%. The track shrinks from the transition zone to the cooling zone 1. In order to improve the flatness of the film surface, the temperature should not drop suddenly during the process of heat setting and cooling. The temperature in the transition zone is 140-190℃, and the temperature in the cooling zone is 70-130℃.

[0036] Furthermore, the reflective film provided by the present invention has good film surface flatness, because after the film is treated by the horizontal stretching process, the film has sufficient crystallization and strength to resist film deformation; at the same time, the molecular structure of the amorphous region of the film is converted from a higher energy state to a lower energy state, and the film is not prone to post-deformation.

[0037] The film making process in the embodiment is as follows: S1 casting and S2 stretching film forming steps, wherein: the longitudinal stretching ratio is 3.6, the transverse stretching ratio is 3.8, the temperatures of the transverse drawing heat setting zones 1-5 are 200 / 225 / 228 / 228 / 220°C respectively, the transition zone temperature is 160°C, and the cooling zone temperature is 110 / 70°C respectively; the track shrinkage is 2.5%, and the total thickness of the reflective film is 188μm.

[0038] The formula of the A layer and the B layer of each embodiment is shown in Table 1 below. The functional masterbatch in the A layer is a silica masterbatch, specifically FG613, selected from Sinopec Yizheng Chemical Fiber Co., Ltd., the toughening agent is PETG, and the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate. The incompatible resin masterbatch in the B layer is a COC masterbatch, which is specifically made of 20% cycloolefin non-crystalline copolymer, 3% POE-g-GMA and 77% PET chips processed by a venting twin-screw granulator. The cycloolefin non-crystalline copolymer is made by copolymerization of ethylene and norbornene monomer (NB) under the action of a metallocene catalyst system, and its glass transition temperature is 140°C; the melt index MFR (2.16kg, 260°C) is 40g / 10min; and the yellow index YI is 2.

[0039] Table 1 Formulation of Examples 1-14

[0040]

[0041] Comparative Example 1

[0042] The formula of the reflective film A layer: FG613 content 46%, antistatic agent 2%, PET slices 50%, toughening agent 2%, the above percentages are the weight percentages of the A layer. The formula of the reflective film B layer: TiO2 masterbatch content 20%, TPX masterbatch 50% (specifically made by 20% TPX, 3% POE-g-GMA and 77% PET slices through a venting twin-screw granulator), PET slices 30%, the above percentages are the weight percentages of the B layer.

[0043] Performance Testing:

[0044] Reflectivity: According to GB / T3979-2008 standard, the reflectivity was tested by ColorQuest XE spectrophotometer (manufactured by Hunterlab) under D65 light source with integrating sphere d / 8° structure. The reflectivity data is the weighted average of the reflectivity at every 10nm wavelength from 400 to 700nm, and the weight corresponds to the energy distribution curve of D65 light source.

[0045] Glossiness: According to GB / T 9754-2007 standard, use ZGM 1020 60° medium gloss instrument to measure. Select a reflective film with a flat surface, size 3*5cm, and take each sample 3 times, once on the left, middle and right. Calibrate the instrument before testing the sample. After calibration, test the front and back sides of 3 films respectively, record the data, and calculate the average value.

[0046] Density test: Take a 10*10cm size sample from each and place it on a density meter for testing. Take 3 samples from each sample and record the average value.

[0047] Stiffness: Use DR-B214 stiffness tester for testing. Cut the sample into small strips of length × width = 70mm × 38mm, place the sample on the instrument for testing, read the stiffness value displayed on the screen, measure 3 strips in the longitudinal direction (MD) and transverse direction (TD) for each sample, and take the smallest value among the 3 as the stiffness value in that direction.

[0048] The performance test results of the embodiments and comparative examples are shown in Table 2 below.

[0049] Table 2 Performance table of Examples 1-14 and Comparative Example 1 (188 μm)

[0050]

[0051]

[0052] From the performance data of the test in Table 2, it can be concluded that the reflective film prepared in the embodiment of the present invention, while ensuring the reflectivity (>96%), has significantly higher stiffness in the MD and TD directions than that in comparative example 1, which is above 3.8 mN.m. No creases will appear during the use of a large-size backlight module, thus meeting the application requirements.

[0053] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made based on the content of the present invention are included in the patent scope of the present invention.

Claims

1. A high stiffness white polyester film, the reflective film is an ABA three-layer co-extrusion structure, characterized in that: Layer A is a uniform light layer, comprising the following percentages of components: 10-96% functional masterbatch, 0-86% polyester chips, 2% antistatic masterbatch and 2% toughening agent; Layer B is a functional layer, comprising the following percentages of components: 40-60% incompatible resin masterbatch, 8-40% inorganic functional masterbatch and 0-52% polyester chips; the percentages are weight percentages.

2. The high stiffness white polyester film according to claim 1, characterized in that: The incompatible resin masterbatch is a POE-g-GMA modified cycloolefin non-crystalline copolymer, which is made by processing 20% ​​of cycloolefin non-crystalline copolymer, 3% of POE-g-GMA and 77% of PET chips through a venting twin-screw granulator.

3. The high stiffness white polyester film according to claim 2, characterized in that: The cycloolefin non-crystalline copolymer is prepared by copolymerization of ethylene and norbornene monomer (NB). The glass transition temperature of the cycloolefin non-crystalline copolymer is 140°C; the melt index MFR (2.16kg, 260°C) is 40g / 10min; and the yellowness index YI is 2.

4. The high stiffness white polyester film according to claim 1, characterized in that: The inorganic functional masterbatch in the B layer is made of 60% titanium dioxide, 1% PEG-20000 and 39% PET chips through a venting twin-screw granulator. The titanium dioxide is rutile titanium dioxide, the particles are spherical, and the average particle size is 200nm.

5. The high stiffness white polyester film according to claim 1, characterized in that: The functional masterbatch in the A layer is at least one of silicon dioxide, titanium dioxide, calcium carbonate, barium sulfate and aluminum oxide.

6. The high stiffness white polyester film according to claim 1, characterized in that: The antistatic masterbatch in the A layer is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; and the toughening agent is PETG.

7. The high stiffness white polyester film according to claim 1, characterized in that: The polyester chips include at least one of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate.

8. The high stiffness white polyester film according to claim 7, characterized in that: The thickness of the reflective film is 50-300 μm.

9. A method for preparing a high stiffness white polyester film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1, casting: the polyester chips, inorganic functional masterbatch, and incompatible resin masterbatch in the B layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; at the same time, the polyester chips, antistatic agent, functional masterbatch, and toughening agent in the A layer are weighed according to the formula ratio by a weight loss scale device and then fed into a vented twin-screw extruder, and after high-temperature melting, vacuumization, and filtration, they are introduced into a T-die through a melt pipe; the raw materials of the B layer and the A layer are laminated into three layers in the die head, and then co-extruded from the die head mouth, and quickly attached to the surface of the cooling drum with the help of an electrostatic adsorption device to obtain an amorphous thick sheet; S2, stretching film: the amorphous thick sheet obtained in step S1 is first preheated by a longitudinal stretching roller, and then longitudinally stretched 3.0-3.6 times between the stretching fast and slow rollers under the auxiliary heating of an infrared lamp, and a single-stretched film is obtained after cooling. The single-stretched film is introduced into the clamps on both sides of the transverse stretching entrance and clamped, and enters the transverse stretching system, transversely stretched 3.4-4.0 times, heat-set for 10-30 seconds, fully crystallized, and then the track is narrowed and cooled, and then trimmed, rolled, and slit to obtain a finished reflective film.

10. The method for preparing a high stiffness white polyester film according to claim 9, characterized in that: In the step S2, during the process from heat setting to cooling of the transverse drawing, the heat setting temperature is 190-235°C; after crystallization, the track shrinks by 1%-5%, and the track shrinks from the transition zone to the cooling zone 1. During the process from heat setting to cooling, the temperature gradually decreases; the temperature of the transition zone is 140-190°C, and the temperature of the cooling zone is 70-130°C.

Citation Information

Patent Citations

  • Reflective film and its preparation method

    CN110927846B

  • A crease-resistant coated reflective film and its preparation method

    CN114779377B

  • Overfeeding type thin film drawing process

    CN105252752A

  • Preparation method of low-thermal-shrinkage polyester polyester reflective film

    CN106671544A

  • Laminating reflective coating and preparation method thereof

    CN106903958A